2014
DOI: 10.1007/s10461-014-0834-8
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provider Attitudes and Beliefs About People Living with HIV: Initial Validation of the Health Care Provider HIV/AIDS Stigma Scale (HPASS)

Abstract: HIV stigma is a pressing concern for people living with HIV, and particularly when it is perpetuated by health care providers, as it may affect quality of life and access to health care services. The current study describes the development and initial validation of a contextually appropriate HIV stigma scale for health care providers in North America. A ground-up qualitative approach was used to develop the scale, and it was assessed psychometrically with health care trainees across Canada. The measure demonst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 38 publications
2
56
0
3
Order By: Relevance
“…In the current study, the total scale demonstrated excellent internal consistency (Cronbach's alpha = .94), as did each subscale (Cronbach's alphas = .91, .82, and .92 for prejudice, stereotypes, and discrimination, respectively). The scale has demonstrated good test-retest reliability (r = .93, p < .001), convergent validity with other measures of HIV-related stigma, and divergent validity with a scale of empathy associated with HIV (Wagner et al, 2014).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the current study, the total scale demonstrated excellent internal consistency (Cronbach's alpha = .94), as did each subscale (Cronbach's alphas = .91, .82, and .92 for prejudice, stereotypes, and discrimination, respectively). The scale has demonstrated good test-retest reliability (r = .93, p < .001), convergent validity with other measures of HIV-related stigma, and divergent validity with a scale of empathy associated with HIV (Wagner et al, 2014).…”
Section: Methodsmentioning
confidence: 91%
“…Two hundred and thirty-four medical and nursing students from across Canada participated in the study (see Wagner, Hart, McShane, Margolese, & Girard, 2014, for a detailed description of the study). They were recruited to participate in an online study to examine health care trainee attitudes and beliefs about HIV and related variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resource was adapted from the previously validated Healthcare provider HIV/AIDS stigma scale (14) in partnership with Dr. Anne Wagner, who led the research team that devised the original stigma scale, to incorporate a broader range of STBBIs and reflect the continual shift towards a more integrated approach to STBBIs (15). The revised tool was psychometrically validated following two rounds of pilot testing with 144 service providers from across Canada.…”
Section: Self-assessment Toolmentioning
confidence: 99%
“…Usually because of the behaviors that do not comply with the values and beliefs shared by the society, the patients that possess the disease have difficulty accessing their healthcare rights for they are being judged by the society. [3][4][5] People with HIV / AIDS suffer from stigmatization, obstacles to participation in work, education, social and cultural life. Patients may experience physical and emotional harm with discrimination, embarrassment, mockery, deprivation of right, loss of roles / relationships.…”
mentioning
confidence: 99%